Akumulasi dan alokasi modal fisik: Katalisator pertumbuhan ekonomi di kawasan pedesaan Indonesia - Faulina, Elsa Sendy Nur (Maliki Interdisciplinary Journal, 2025)
Economic growth in rural areas in Indonesia is influenced by various factors, including the accumulation and allocation of physical capital such as infrastructure, technology, and means of production. Physical capital plays a critical role in increasing agricultural productivity, expanding market access, and encouraging economic diversification in rural areas. This article examines the relationship between physical capital accumulation and economic growth in rural areas, and assesses the effectiveness of physical capital allocation implemented by the government and the private sector. Using secondary data from the Central Statistics Agency (BPS) and the Ministry of Public Works and Public Housing (PUPR), this study evaluates the impact of infrastructure, technology, and capital investment on rural productivity in various regions in Indonesia. The study findings indicate that increasing physical capital, especially in terms of transportation infrastructure and agricultural technology, has a significant impact on local economic growth. However, the inequality in the distribution of physical capital across regions remains a major challenge to achieving inclusive growth. Therefore, this study recommends a more coordinated and comprehensive policy, focusing on equal access to physical capital, sustainable infrastructure development, and stronger collaboration between the government and the private sector.